2023
DOI: 10.1101/gad.351085.123
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive mapping of cell fates in microsatellite unstable cancer cells supports dual targeting of WRN and ATR

Dali Zong,
Natasha C. Koussa,
James A. Cornwell
et al.

Abstract: Addiction to the WRN helicase is a unique vulnerability of human cancers with high levels of microsatellite instability (MSI-H). However, while prolonged loss of WRN ultimately leads to cell death, little is known about how MSI-H cancers initially respond to acute loss of WRN—knowledge that would be helpful for informing clinical development of WRN targeting therapy, predicting possible resistance mechanisms, and identifying useful biomarkers of successful WRN inhibition. Here, we report the construction of an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Our findings in this study suggest that MMR deficiency/MSI-H are also useful biomarkers to guide patient stratification for treatment with ATR inhibitors, which are already extensively tested in clinical trials ( Sundar et al 2017 ; Ngoi et al 2022 ). Our findings are consistent with those from an independent study by the Nussenzweig laboratory ( Zong et al 2023 ), who also found that ATRi preferentially kills MMR-d/MSI-H tumor cells. Both studies suggest that the use of MMR deficiency/MSI-H as biomarkers to guide ATRi therapy may rapidly extend the use of ATRi in patients and improve the treatment of MMR-d/MSI-H tumors.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings in this study suggest that MMR deficiency/MSI-H are also useful biomarkers to guide patient stratification for treatment with ATR inhibitors, which are already extensively tested in clinical trials ( Sundar et al 2017 ; Ngoi et al 2022 ). Our findings are consistent with those from an independent study by the Nussenzweig laboratory ( Zong et al 2023 ), who also found that ATRi preferentially kills MMR-d/MSI-H tumor cells. Both studies suggest that the use of MMR deficiency/MSI-H as biomarkers to guide ATRi therapy may rapidly extend the use of ATRi in patients and improve the treatment of MMR-d/MSI-H tumors.…”
Section: Discussionsupporting
confidence: 93%
“…Another striking example of induced synthetic lethality and antitumor immunity after ATR inhibition has been recently reported regarding Mismatch Repair (MMR) deficient cancer cells [ 112 ]. Also, in tumors with high levels of microsatellite instability (MSI-H) that are characterized by decreased levels of WRN helicase, it has been shown that ATR inhibition may potentiate tumor cell death [ 113 ]. MSI-H tumors may also present mutations in the ARID1A chromatin remodeling protein that plays a substantial role in DNA repair [ 114 ].…”
Section: The Atr Pathway As a Therapeutic Targetmentioning
confidence: 99%